PEC photoelectrode of n-GaAs / CuSCN / glycerol-coated PEDOT: PSS and preparation and application of PEC photoelectrode of n-GaAs / CuSCN / glycerol-coated PEDOT: PSS

By constructing a CUSCN cavity transmission layer and glycerin @pedot: PSS heterogeneous knot on the N-GaaS optical electrode, the problem of low transmission efficiency of the existing photochemical carrier is solved, and the performance of high-efficiency photovoltaic catalytic hydrogen making performance is achieved, and the performance of hydrogenation of photoelectric catalytic, and and also Reduce preparation costs.

CN119372691APending Publication Date: 2025-01-28SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411321486.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing photoelectrodes have low carrier transmission efficiency, high cost and no obvious performance improvement in the process of PEC decomposition of water hydrogen production.

Method used

Adopt PEC optical electrodes based on N-Gaas/CUSCN/Glycerin @pedot: PSS, build heterogeneous knots through the suspension method, and add CUSCN as a cave transmission layer between them to improve carrier transmission efficiency.

Benefits of technology

The efficiency of high carrier transmission is achieved, significantly improved the hydrogen analysis performance of photochemical electrodes, reduced preparation costs, and provided a new type of semiconductor composite catalytic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372691A_ABST
    Figure CN119372691A_ABST
Patent Text Reader

Abstract

The invention discloses a PEC photoelectrode of n-GaAs / CuSCN / glycerin coated PEDOT: PSS, and a preparation method and an application of the PEC photoelectrode of n-GaAs / CuSCN / glycerin coated PEDOT: PSS. The PEC photoelectrode comprises an n-GaAs substrate and a glycerol doped PEDOT: PSS (poly (3, 4-ethylenedioxythiophene): poly (styrenesulfonate)) conductive According to the PEC photoelectrode of n-GaAs / CuSCN / glycerol coated PEDOT: PSS provided by the invention, the conductivity of the PEC photoelectrode can be efficiently and simply enhanced, and carrier migration is promoted; meanwhile, the final product composite structure enhances the photon-generated carrier separation and transfer efficiency, and the photoelectric conversion efficiency can be remarkably improved. The PEC photoelectrode of the n-GaAs / CuSCN / glycerol-coated PEDOT: PSS has strong carrier migration ability, has strong sunlight utilization rate, and is suitable for hydrogen production by photoelectrolysis of water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photoelectrode materials, and in particular to a suspension coating method based on CuSCN on an n-GaAs substrate, a glycerol@PEDOT:PSS doped suspension coating final product composite structure and applications thereof. Background Art

[0002] Photoelectrochemical (PEC) water splitting can effectively convert and store solar energy into clean, renewable hydrogen energy. In recent years, III-V compound nanorods have broad application prospects in the field of PEC water splitting. Compared with wide-bandgap semiconductors GaN, AlN, GaAs, InN and other narrow-bandgap semiconductors, they show stronger light absorption and photoresponse. Among them, the bottom position of the conduction band of n-GaAs (CBM: 4.00 eV vs. Vac) is very suitable for PEC hydrogen evolution photoelectrodes, and it can form a type II pn heterojunction with glycerol@PEDOT:PSS. However, due to problems such as surface state accumulation and accumulation of photogenerated carriers, the PEC water splitting performance of photoelectrodes has a large bottleneck. The current hydrogen production efficiency is not high, and there is still a certain distance from industrial production.

[0003] Constructing a heterojunction is an effective means to improve device performance. Currently, the commonly used methods to improve the performance of PEC water splitting are as follows: Existing literature discloses an application example of using sulfides such as (NH4)2S and MoS2 to jointly passivate III-V semiconductor GaAs / InGaP2 (Lim, H., Young, JL, Geisz, JF et al. Highperformance III-V photoelectrodesfor solar water splitting viasynergistically tailored structure and stoichiometry. Nat Commun 10, 3388(2019).). This method reduces the overpotential and increases the photocurrent, and to a certain extent slows down the loss of photogenerated carriers caused by surface dangling bonds. However, the passivation layer sulfide introduced by this method has poor stability in the air, and it is necessary to rely on high-concentration multiple sulfide solutions for joint passivation to achieve long-term and efficient PEC photoelectrolysis of water.

[0004] Existing literature discloses an application example of preparing InGaP / GaAs heterojunction on a flexible substrate by epitaxial lift-off and transfer technology (Varadhan P, Fu HC, Kao YC, et al. An efficient and stable photoelectrochemical system with 9% solar-to-hydrogen conversion efficiency via InGaP / GaAs double junction[J]. Nature Communications, 2019, 10(1)). The authors successfully assembled an "artificial green leaf" device and achieved a 9% STH efficiency. The device has the characteristics of high efficiency, stability and flexibility. The PEC photoelectrode of the InGaP / GaAs photoanode exhibits a 9% STH efficiency and stability of up to 150 hours. However, the preparation method of this heterojunction is relatively complicated, and the equipment and time costs required are very high, which is not conducive to the large-scale application of the technology. Summary of the invention

[0005] In order to overcome the bottlenecks of low carrier transfer efficiency, high technology cost, and insignificant improvement effect, the purpose of the present invention is to provide a PEC photoelectrode based on n-GaAs / CuSCN / glycerol@PEDOT:PSS and its preparation and application. The preparation method of the present invention has simple process and low cost; at the same time, the product can achieve high carrier transfer efficiency and greatly enhance the hydrogen evolution performance of the photoelectrode, providing a new idea for the preparation of other semiconductor composite catalytic materials.

[0006] The purpose of the present invention is achieved through the following technical solutions.

[0007] A PEC photoelectrode comprises a bottom-up back electrode, an n-GaAs substrate and a glycerol@PEDOT:PSS layer.

[0008] Preferably, there is a hole transport layer between the n-GaAs substrate and the glycerol@PEDOT:PSS layer; the material of the hole transport layer is CuSCN.

[0009] Preferably, the doping volume ratio of the glycerol@PEDOT:PSS layer is glycerol:PEDOT:PSS=2:1-1:1, more preferably 2:1, 1.5:1, 1:1, and most preferably 2:1.

[0010] Preferably, the thicknesses of the back electrode, the n-GaAs substrate, the glycerol@PEDOT:PSS layer, and the hole transport layer are 80-120 nm, 250-300 μm, 100-150 nm, and 100-150 nm, respectively.

[0011] Further preferably, the thicknesses of the back electrode, the n-GaAs substrate, the glycerol@PEDOT:PSS layer, and the hole transport layer are 120 nm, 300 μm, 100 nm, and 100 nm, respectively.

[0012] Preferably, the n-GaAs substrate is heavily n-type doped gallium arsenide with a doping concentration of 5.1×10 19 cm -3 ~5.8×10 19 cm -3 .

[0013] Preferably, the back electrode is one or more of Ti and Au.

[0014] The method for preparing a PEC photoelectrode as described in any one of the above items comprises the following steps: (1) Suspending CuSCN solution on n-GaAs substrate; (2) Glycerol@PEDOT:PSS is further suspension coated on the n-GaAs / CuSCN obtained in step (1), and then annealed on a hot plate after suspension coating.

[0015] Preferably, in step (1), the n-GaAs substrate is subjected to a cleaning treatment, firstly, organic pollutants on the surface of the substrate are removed by using an organic solvent, then the n-GaAs substrate is treated with hydrochloric acid to treat the surface oxide layer, and finally, it is dried with high-purity dry nitrogen; the organic pollutants on the surface of the n-GaAs substrate are removed by using an organic solvent by spin washing in acetone and anhydrous ethanol in sequence, and then rinsing with water; the concentration of the hydrochloric acid is 5wt%~20wt%.

[0016] Preferably, the n-GaAs substrate in step (1) is heavily n-type doped GaAs with a doping concentration of 5.1×10 19 cm -3 ~5.8×10 19 cm -3 .

[0017] Preferably, the general standard for heavy doping is >1E18cm^-3.

[0018] Preferably, the concentration of the CuSCN solution in step (1) is 0.1 mol / L.

[0019] Preferably, the CuSCN film after suspension coating in step (1) needs to be air-dried at room temperature for 10 minutes.

[0020] Preferably, the specific conditions of the suspension coating process in step (1) are: 30-60s at a rotation speed of 1000-4000rpm / min.

[0021] Further preferably, the specific conditions of the suspension coating process in step (1) are: 30 seconds at a rotation speed of 4000 rpm / min.

[0022] Preferably, in step (2), the glycerol@PEDOT:PSS doping volume ratio is glycerol:PEDOT:PSS=2:1.

[0023] Preferably, the specific suspension coating conditions of the glycerol@PEDOT:PSS in step (2) are as follows: the first step is pre-spinning at a rotation speed of 500-1000 rpm for 5-10 s to shake off larger clusters; the second step is pre-spinning at a rotation speed of 1000-6000 rpm for 30-60 s.

[0024] Further preferably, the specific suspension coating conditions of the glycerol@PEDOT:PSS in step (2) are as follows: the first step is to pre-spin at a rotation speed of 500 rpm for 5 s to shake off larger clusters; the second step is to pre-spin at a rotation speed of 6000 rpm for 30 s.

[0025] Preferably, the specific conditions of the annealing in step (2) are: annealing at 140-160° C. for 10-20 min to remove excess doped glycerol.

[0026] Further preferably, the specific conditions of the annealing in step (2) are: annealing at 140° C. for 10 min to remove excess doped glycerol.

[0027] Application of a PEC photoelectrode as described in any of the above items in photoelectrocatalytic hydrogen production.

[0028] Preferably, the PEC photoelectrode is used in photoelectrolysis of water to produce hydrogen.

[0029] The present invention adopts a suspension coating method to perform multiple suspension coating treatments on an n-GaAs substrate, wherein the n-GaAs substrate is heavily n-type doped gallium arsenide with a doping concentration of 5.1×10 19 cm -3 ~5.8×10 19 cm -3 Through this new suspension coating method, an n-GaAs / glycerol@PEDOT:PSS heterojunction is constructed, and CuSCN is added between them as a hole transport layer to further improve the carrier transport efficiency. The formed n-GaAs / CuSCN / glycerol@PEDOT:PSS heterojunction can effectively improve the performance of photocatalytic hydrogen evolution.

[0030] The present invention utilizes a heterostructure on an electrochemical anode n-GaAs / CuSCN / glycerol@PEDOT:PSS, which is considered to be a convenient, fast, and long-term method to solve the high cost and insufficient carrier driving force. CuSCN is used as a hole transport layer to enhance hole transport. Glycerol@PEDOT:PSS is suspended on the outside of the electrode to construct a heterojunction, further enhancing the carrier transport efficiency. In addition, the introduction of glycerol doping can dissociate the PSS group with poor conductivity in PEDOT:PSS, further enhancing the conductivity of PEDOT:PSS, and ultimately achieving the purpose of improving device performance.

[0031] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The present invention achieves high carrier migration efficiency and possesses a hole transport layer by addressing the shortcomings of the material, providing a new approach for the preparation of other semiconductor composite catalytic materials. It effectively utilizes the high carrier concentration of n-GaAs and effectively solves the problem of limited carrier migration efficiency of a single semiconductor by introducing heterojunction and hole transport layer materials, thereby improving carrier transport efficiency and device performance.

[0032] (2) The method of the present invention is more efficient and economical. The method of constructing heterostructures by suspended coating adopted by the present invention is safer and more thorough than the traditional method of constructing heterostructures; compared with the newer methods such as ALD deposition and MBE growth, the time cost of the present invention is low.

[0033] (3) The composite structure of the final product produced by the present invention can effectively improve the performance of the device for photocatalytic water splitting to produce hydrogen. The traditional hole transport layer construction method, such as chemical deposition, is through vapor deposition such as passive CVD and MBE. The deposition has strict requirements on the substrate and requires specific preparation conditions. The CuSCN film in this system does not require specific conditions, and room temperature suspension coating is more convenient and fast. The separation and transfer of photogenerated carriers in the system are easier, which significantly improves the photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Schematic diagram of the process flow of n-GaAs / CuSCN / glycerol@PEDOT:PSS photoelectrode.

[0035] Figure 2 The light and dark current density-bias curves of n-GaAs / CuSCN / glycerol@PEDOT:PSS, n-GaAs / glycerol@PEDOT:PSS, n-GaAs / CuSCN, and n-GaAs / PEDOT:PSS obtained in Example 1-2 and Comparative Example 1-2 are shown.

[0036] Figure 3ABPE curves of n-GaAs / CuSCN / glycerol@PEDOT:PSS, n-GaAs / glycerol@PEDOT:PSS, n-GaAs / CuSCN, and n-GaAs / PEDOT:PSS obtained in Example 1-2 and Comparative Example 1-2. DETAILED DESCRIPTION

[0037] The directional terms such as up, down, left, right, front, back, front, back, top, bottom, etc. mentioned or may be mentioned in this specification are defined relative to their structure and are relative concepts. Therefore, they may change accordingly according to their different locations and different usage conditions. Therefore, these or other directional terms should not be interpreted as restrictive terms.

[0038] The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present disclosure. Instead, they are merely examples of embodiments consistent with some aspects of the present disclosure.

[0039] The terms used in this disclosure are only for the purpose of describing specific embodiments and are not intended to limit the disclosure. The singular forms of "a", "the" and "the" used in this disclosure are also intended to include plural forms, unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.

[0040] Figure 1 Schematic diagram of the process flow of n-GaAs / CuSCN / glycerol@PEDOT:PSS photoelectrode.

[0041] Example 1 A method for preparing an n-GaAs / CuSCN / glycerol@PEDOT:PSS photoelectrode comprises the following steps: (1) Substrate selection: n-GaAs substrate with a doping concentration of 5.1×10 19 cm -3 .

[0042] (2) Substrate cleaning: First, clean the substrate with acetone and anhydrous ethanol in turn, then use 20wt% hydrochloric acid to remove the oxide layer on the n-GaAs substrate; finally, blow dry with high-purity dry nitrogen with a purity of 5N; (3) 10 μl of a 0.5 mg / ml CuSCN solution was suspended on the n-GaAs substrate. The specific conditions of the suspension coating process were: 30 seconds at a rotation speed of 4000 rpm / min, and then air-dried at room temperature after suspension coating.

[0043] (4) 10 μl of glycerol@PEDOT:PSS solution was suspended on the obtained n-GaAs / CuSCN. The volume ratio of glycerol to PEDOT:PSS in the solution was 2:1. The specific conditions of the suspension coating process were: initial rotation at 500 rpm / min for 5 s and then at 6000 rpm / min for 30 s.

[0044] Example 2 The n-GaAs / glycerol@PEDOT:PSS photoelectrode without the CuSCN hole transport layer comprises the following steps: (1) Substrate selection: n-GaAs substrate with a doping concentration of 5.1×10 19 cm -3 .

[0045] (2) Substrate cleaning: First, clean the substrate with acetone and anhydrous ethanol in turn, then use 20wt% hydrochloric acid to remove the oxide layer on the n-GaAs substrate; finally, blow dry with high-purity dry nitrogen with a purity of 5N; (3) 10 μl of glycerol@PEDOT:PSS solution was suspended on the obtained n-GaAs substrate. The volume ratio of glycerol to PEDOT:PSS in the solution was 2:1. The specific conditions of the suspension coating process were: an initial rotation speed of 500 rpm / min for 5 s and a subsequent rotation speed of 6000 rpm / min for 30 s.

[0046] Comparative Example 1 The method for preparing an n-GaAs / CuSCN photoelectrode without using glycerol-doped PEDOT:PSS comprises the following steps: (1) Substrate selection: n-GaAs substrate with a doping concentration of 5.1×10 19 cm -3 ~5.8×10 19 cm -3 .

[0047] (2) Substrate cleaning: First, clean the substrate with acetone and anhydrous ethanol in turn, then use 20wt% hydrochloric acid to remove the oxide layer on the n-GaAs substrate; finally, blow dry with high-purity dry nitrogen with a purity of 5N; (3) 10 μl of a 0.5 mg / ml CuSCN solution was suspended on the n-GaAs substrate. The specific conditions of the suspension coating process were: 30 seconds at a rotation speed of 4000 rpm / min, and then air-dried at room temperature after suspension coating.

[0048] Comparative Example 2 The method for preparing an n-GaAs / PEDOT:PSS photoelectrode without using glycerol-doped PEDOT:PSS and without using CuSCN comprises the following steps: (1) Substrate selection: n-GaAs substrate with a doping concentration of 5.1×10 19 cm -3 ~5.8×10 19 cm -3 .

[0049] (2) Substrate cleaning: First, clean the substrate with acetone and anhydrous ethanol in turn, then use 20wt% hydrochloric acid to remove the oxide layer on the n-GaAs substrate; finally, blow dry with high-purity dry nitrogen with a purity of 5N; (3) 10 μl of PEDOT:PSS solution was suspended on the obtained n-GaAs substrate. The specific conditions of the suspension coating process were: an initial rotation speed of 500 rpm / min for 5 s and a subsequent rotation speed of 6000 rpm / min for 30 s.

[0050] The composite structure of the final product prepared in Example 1-2 and the final product prepared in Comparative Example 1 are applied to photoelectrolysis of water to produce hydrogen. The products need to be made into photoelectrodes. The specific steps are as follows: (i) using electron beam evaporation to deposit metal layers Ti and Au to form an ohmic contact with the back of n-GaAs; (ii) then connecting the metal layer with a metal wire and sealing it with liquid tin; (iii) Protect the entire metal backside with insulating epoxy; (iv) Use an electrochemical workstation to perform photoelectrochemical tests as follows: ①Use sodium sulfate solution with pH=6.09 as the electrolyte; ② The prepared photoelectrode was used as the cathode, the Ag / AgCl electrode was used as the reference electrode, and the Pt sheet was used as the anode; ③ Xe lamp with power of 300 W (light intensity ~100 mW / cm 2 ) as the light source.

[0051] The light-dark current density-bias curve is obtained by testing, see Figure 2 The final product composite structure prepared in Example 1, namely n-GaAs / CuSCN / glycerol@PEDOT:PSS photoelectrode, has a photocurrent density of 20.24 mA / cm at 1.23 V vs. RHE bias. 2 , the dark current density is 0.36 mA / cm 2 , the net photocurrent density is 19.88 mA / cm 2 , optical gain up to 5522.22%, APBE (see Figure 3 ) reaches a maximum of 13.7%, and the STH efficiency is 19.6%.

[0052] The light-dark current density-bias curve is obtained by testing, see Figure 2 The photocurrent density of the n-GaAs / glycerol@PEDOT:PSS photoelectrode prepared in Example 2 was 17.55 mA / cm at 1.23 V vs. RHE bias. 2 , the dark current density is 1.14 mA / cm 2 , the net photocurrent density is 17.37 mA / cm 2 , optical gain up to 1439.40%, APBE (see Figure 3 ) reaches a maximum of 12.7%, and the STH efficiency is 12.8%.

[0053] The light-dark current density-bias curve is obtained by testing, see Figure 2 The photocurrent density of the n-GaAs / CuSCN photoelectrode prepared in Comparative Example 1 was 18.12 mA / cm at 1.23 V vs. RHE bias. 2 , the dark current density is 0.49 mA / cm 2 , the net photocurrent density is 17.36 mA / cm 2 , optical gain reaches 3598% APBE (see Figure 3 ) reaches a maximum of 10.9%.

[0054] The light-dark current density-bias curve is obtained by testing, see Figure 2 The photocurrent density of the n-GaAs / PEDOT:PSS photoelectrode prepared in Comparative Example 2 was 9.89 mA / cm at 1.23 V vs. RHE bias. 2 , the dark current density is 0.38 mA / cm 2 , the net photocurrent density is 9.51 mA / cm 2 , optical gain up to 2503%, APBE (see Figure 3 ) reaches a maximum of 7.1%.

[0055] The above-mentioned embodiments and comparative examples show that the performance of n-GaAs / CuSCN / photoelectrode is significantly improved after the introduction of doped glycerol@PEDOT:PSS, and the photocurrent is further improved after the addition of the CuSCN hole transport layer.

[0056] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A PEC photoelectrode, characterized in that: It includes the bottom-up back electrode, n-GaAs substrate and glycerol@PEDOT:PSS layer.

2. A PEC photoelectrode according to claim 1, characterized in that: There is also a hole transport layer between the n-GaAs substrate and the glycerol@PEDOT:PSS layer; the material of the hole transport layer is CuSCN.

3. A PEC photoelectrode according to claim 1 or 2, characterized in that: The doping volume ratio in the glycerol@PEDOT:PSS layer is glycerol:PEDOT:PSS=2:1-1:

1.

4. A PEC photoelectrode according to claim 3, characterized in that: The thicknesses of the back electrode, the n-GaAs substrate, the glycerol@PEDOT:PSS layer, and the hole transport layer are 80-120nm, 250-300μm, 100-150nm, and 100-150nm, respectively.

5. A PEC photoelectrode according to claim 1, characterized in that: The n-GaAs substrate is heavily n-type doped gallium arsenide with a doping concentration of 5.1×10 19 cm -3 ~5.8×10 19 cm -3 .

6. A PEC photoelectrode according to claim 1, characterized in that: The back electrode is one or more of Ti and Au.

7. The method for preparing a PEC photoelectrode according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Suspending CuSCN solution on n-GaAs substrate; (2) Glycerol@PEDOT:PSS is further suspension coated on the n-GaAs / CuSCN obtained in step (1), and then annealed on a hot plate after suspension coating.

8. The method for preparing a PEC photoelectrode according to claim 7, characterized in that: The specific conditions of the suspension coating process in step (1) are: 30 seconds at a speed of 1000-4000 rpm / min; The specific suspension coating conditions of the glycerol@PEDOT:PSS in step (2) are as follows: the first step is to pre-spin at a speed of 500-1000 rpm for 5-10 s to shake off larger clusters; the second step is to pre-spin at a speed of 1000-6000 rpm for 30-60 s.

9. The method for preparing a PEC photoelectrode according to claim 7, characterized in that: The specific conditions of the annealing in step (2) are: annealing at 140-160° C. for 10-20 min to remove excess doped glycerol.

10. Use of a PEC photoelectrode according to any one of claims 1 to 6 in photoelectrocatalytic hydrogen production.